2018
DOI: 10.1136/tobaccocontrol-2017-054198
|View full text |Cite
|
Sign up to set email alerts
|

Flavour capsule cigarette use among US adult cigarette smokers

Abstract: Flavour capsule cigarettes use is highest in young adults, particularly Hispanics. Young adult predominance, lower level of addiction symptoms and emphasis on pack design by flavour capsule users suggest that these products may be positioned as starter products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…35,36,73,74,78,79,91,92 For the current review, 15 publications were identified as including information on smoking frequency. 46,67,83,86,89,[93][94][95][96][97][98][99][100][101][102] Nearly all of the new studies provide evidence of either no difference or less frequent smoking among menthol smokers. Studies supporting that menthol smokers are not more likely than nonmenthol smokers to be daily smokers or to smoke more frequently include multiple publications with adjusted analyses of large and representative survey data 35,67,74,79,83,92,97 and unadjusted analyses from other representative and large studies.…”
Section: Smoking Frequencymentioning
confidence: 96%
See 4 more Smart Citations
“…35,36,73,74,78,79,91,92 For the current review, 15 publications were identified as including information on smoking frequency. 46,67,83,86,89,[93][94][95][96][97][98][99][100][101][102] Nearly all of the new studies provide evidence of either no difference or less frequent smoking among menthol smokers. Studies supporting that menthol smokers are not more likely than nonmenthol smokers to be daily smokers or to smoke more frequently include multiple publications with adjusted analyses of large and representative survey data 35,67,74,79,83,92,97 and unadjusted analyses from other representative and large studies.…”
Section: Smoking Frequencymentioning
confidence: 96%
“…6,36,44,46,49,50,51,62,67,75,84,86,98,102,[108][109][110][111][112] Many of the newly identified analyses report no difference in TTFC among menthol and nonmenthol smokers overall and in a number of subgroups. 36,46,49,50,62,86,98,102,[108][109][110] Studies supporting that menthol smokers have the same or later TTFC as nonmenthol smokers include numerous publications from large or representative studies with adjusted results 6,36,44,49,67,79,107,109,110 and unadjusted results from other large or representative surveys. 73,87,89,91,93,96 Some publications have reported discordant TTFC results (i.e., no difference and longer or shorter TTFC).…”
Section: Smoking Frequencymentioning
confidence: 99%
See 3 more Smart Citations